Oncologic outcomes following radical prostatectomy in the active surveillance era - Louis, Alyssa S.; Kalnin, Robin; Maganti, Manjula; Pintilie, Melania; Matthew, Andrew G; Finelli, Antonio; Zlotta, Alexandre R Zlotta R; Fleshner, Neil; Kulkarni, Girish; Hamilton, Robert; Jewett, Michael; Robinette, Michael; et al. (Canadian Urological Association Journal, 2013)
Objective: In this study, we examine the oncologic outcomes of men with low, intermediate and high preoperative risk for prostate cancer treated with radical prostatectomy prior to and during the active surveillance era. Methods: We analyzed records from patients who underwent radical prostatectomy at our Canadian tertiary care facility from 2000 to 2012. Patients were stratified by D’Amico preoperative risk category and by year of treatment. Biochemical recurrence-free survival was estimated using the Kaplan-Meier method. Results: We included 2643 consecutive patients in our analysis. The proportion of men with low-risk disease undergoing radical prostatectomy decreased from 2007 onwards coincident with the implementation of an active surveillance strategy in our institution. Men with low-risk and high-risk disease showed significantly worse biochemical outcomes from 2007 to 2012 compared to 2000 to 2006 (p < 0.05), while men with intermediate-risk prostate cancer showed no significant differences (p = 0.27). Within the low-risk cohort, the later treatment group displayed significantly lower age, pre-treatment prostate specific antigen and tumour volume and significantly higher testosterone and body mass index. Conclusions: The time period corresponding with the implementation of active surveillance at our institution corresponded with significant deterioration of biochemical outcomes in the low- and high-risk groups. This suggests that the men with most favourable disease deferred treatment, whereas men with worse preoperative disease characteristics were increasingly treated with radical prostatectomy in the past 6 years perhaps to their benefit.